THE ROLE OF THE OMBUDSMAN OF THE INDONESIAN REPUBLIC IN WEST NUSA TENGGARA IN PROMOTING THE LOCAL GOVERNMENT COMPLIANCE TOWARD THE ACT NO. 25 OF 2009 CONCERNING PUBLIC SERVICE - Hakim, Adhar (Jurnal IUS (Kajian Hukum dan Keadilan), 2015)
The research aims to study the application of the role of the Ombudsman of the Indonesian Republic in West Nusa Tenggara in promoting the local government compliance toward the Act No. 25 of 2009 concerning public service and analyze the policies to strengthen the function and the role of the Ombudsman of the Indonesian Republic. This is a normative research. It begins with a statutory analysis to explain the function and the role of the Ombudsman of the Indonesian Republic to control public service in the province of West Nusa Tenggara. This research applies statutory, conceptual, and socio-legal approaches.Â  This research shows that the role of the Ombudsman of the Indonesian Republic in promoting the local government compliance toward the Act No. 25 of 2009 concerning public service relates to some constitutional agenda of government to support local government to conduct bureaucracy reform, good government enforcement, and ascertaining public right to control government. Therefore, it needs constitutional basis. Keywords: Strengthening Role, Compliance, Local Government